Security Protocols XVI 16th International Workshop, Cambridge, UK, April 16-18, 2008. Revised Selected Papers - Christianson, Bruce; Malcolm, James A.; Matyas, Vashek; Roe, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 16th International Workshop on Security Protocols, SP 2008, held in Cambridge, UK, in April 2008. The 17 revised full papers presented together with edited transcriptions of some of the discussions following the presentations have gone through multiple rounds of reviewing, revision, and selection. The theme of this workshop was (3z(BRemodelling the Attacker(3y (Bwith the intention to tell the students at the start of a security course that it is very important to model the attacker, but like most advice to the young, this is an oversimplification. Shouldn$1 (Bt the attacker$1 (Bs capability be an output of the design process as well as an input? The papers and discussions in this volume examine the theme from the standpoint of various different applications and adversaries.s
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Data encryption (Computer science).; Information systems; Computers -- Law and legislation; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Operating Systems; Information Systems Applications (incl.Internet).; Legal Aspects of Computing